Pengalaman Perajin Tenun Ikat di Tengah Pandemi Covid-19 di Sentra Industri Kecil Kabupaten Lamongan - Muhammad Nouvan Zahid (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
The subject of this research is the weaving craftsmen in Lamongan Regency. The object being analyzed is in the form of work experience of the weaving craftsmen during the Covid-19 pandemic. The purpose of writing this article is to construct their experiences so as to create a mutual consensus among weaving artisans about their work experiences during the Covid-19 pandemic. This article is the result of research conducted at the small weaving center of Lamongan Regency, involving several ikat craftsmen. The approach used is qualitative using phenomenological studies. The data collection process was carried out by interviewing techniques and still applying strict health protocols. After exploring the work experience of craftsmen in the midst of a pandemic, negative and positive impacts were found in the center of the small weaving industry in Lamongan Regency. The negative impact of working during the Covid-19 pandemic was a significant reduction in income and the profits that were made to decrease drastically to the point of loss. The positive impact felt by artisans during the Covid-19 pandemic is almost non-existent. However, it turns out that without realizing it, the crafters are getting used to implementing a healthy life and experiencing advances in mastery of digital technology